The microscopic fungi of orchid species in the Őrség National Park - Jandrasits, L.; Fischl, G. (International Journal of Horticultural Science, 2009)
The wild orchids growing in Hungary are some of the most decorative and interesting members of the country’s flora. The majority of species are rarely spotted, and some are only found in very few habitats, though others are quite common .All the species known in Hungary are protected, and 1 1 species are strictly protected. Itis thus important to monitor the health status of these plants, to determine what diseases affect them, what pathogens are found on them and how severely they are infected, and to take the necessary precautionary measures. Eleven of the 14 orchid species occurring in the 6rseg National Park were included in the study and the presence of microscopic fungi was detected on eight of these. Pathogenic species were found on lesser butterfly orchid (Platanthera bifolia), green-winged orchid (Orchis morio), burnt orchid (Orchis ustulara), sword-leaved helleborine (Cephalanthera longifolia), common twayblade (Listera ovata), autumn lady’s-tresses (Spiranthes spiralis), western marsh orchid (Dacrylorhiza majalis) and broad-leaved helleborine (Epipactis helleborine). A detailed account is given of the symptoms of major diseases and of the microscopic traits of the pathogens. An attempt was made to determine to what extent the pathogenic fungal species found on protected orchid species influence the lives of these plants. Current knowledge on this subject is extremely deficient, as practically no data are available from Hungary.